Use of intranasal povidone-iodine packing in the management of infectious rhinosinusitis in three cats - Paul J Sorrentino; Sandra L MacArthur (Journal of Feline Medicine and Surgery Open Reports)
Case series summary Described are three cats diagnosed with rhinosinusitis secondary to Mycobacterium bouchedurhonense , Aspergillus species and Alternaria species, respectively. Medical records were retrospectively reviewed to identify cats with decreased nasal airflow and mucopurulent discharge that failed to improve on antibiotic therapy of 3 months or longer duration. Surgical debridement was followed by nasal packing using 5% povidone-iodine saturated umbilical tape, which was replaced at 24 h postoperatively. At 48 h postoperatively, the rhinotomy site was closed. Systemic therapy continued in the postoperative period. All cases were minimally responsive to previous medical management. History, signalment, clinical signs, diagnostic findings, treatment, and short- and long-term outcomes were retrieved. All cats were middle-aged with outdoor access and had clinical signs that commenced during the summer months. CT revealed turbinate destruction and soft tissue densities within the nasal passages. The otic apparatuses and calvaria were intact in all cats before surgery. A repeat CT examination revealed an improvement of the proliferative tissue identified in preoperative imaging in all cases. All cats achieved successful interruption of nasal discharge and restoration of nasal airflow with follow-up times of up to 16 months postoperatively. Relevance and novel information To the authors’ knowledge, this is the first report of the use of intranasal povidone-iodine packing in cats for the management of infectious rhinosinusitis. Surgical debridement and intranasal packing in addition to systemic therapy were successful in restoring nasal airflow and resolving nasal discharge in all cats with long-term follow-up.